2021
DOI: 10.1038/s41598-021-86446-1
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of biochar and zeolite used for remediation of soil contaminated with toxic heavy metals

Abstract: Biochar and zeolite are widely used in the remediation of soil contaminated with toxic heavy metals. However, the interaction of these amendments and their effects on grass productivity have not been comprehensively summarized. The aim of this study was to investigate the biological effects of zeolite and biochar used as soil amendments in the process of remediating soil contaminated with Cd, Pb and Zn. In a pot experiment, the following treatments were applied: zeolite, biochars produced at temperatures of 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…According to Kapetanions and Loizidou (1992), Carling et al (1998), and Radziemska et al (2013), the addition of zeolite to soil showed positive effects on Solanum lycopersicum L., Chrysanthemum L., and Zea mays L. growth. Głąb et al (2021) found that synthetic zeolite, obtained by a hydrothermal method from coal fly ash, was a much more effective soil amendment than two types of biochars in the soil remediation process. Higher yields of the above‐ground biomass of Festuca arundinacea Schreb., and Dactylis glomerata L., were observed when zeolite was applied either alone or in a mixture with biochars and interaction between zeolite and biochars were also excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kapetanions and Loizidou (1992), Carling et al (1998), and Radziemska et al (2013), the addition of zeolite to soil showed positive effects on Solanum lycopersicum L., Chrysanthemum L., and Zea mays L. growth. Głąb et al (2021) found that synthetic zeolite, obtained by a hydrothermal method from coal fly ash, was a much more effective soil amendment than two types of biochars in the soil remediation process. Higher yields of the above‐ground biomass of Festuca arundinacea Schreb., and Dactylis glomerata L., were observed when zeolite was applied either alone or in a mixture with biochars and interaction between zeolite and biochars were also excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Carling et al (1998), andRadziemska et al (2013), the addition of zeolite to soil showed positive effects on Solanum lycopersicum L., Chrysanthemum L., and Zea mays L. growth Głąb et al (2021). found that synthetic zeolite, obtained by a hydrothermal method from coal fly ash, was a much more effective soil amendment than two types of biochars in the soil remediation process.…”
mentioning
confidence: 99%
“…In turn, zeolites are hydrated aluminosilicates of alkali and alkaline earth minerals, and their structure is characterized by a framework of [SiO 4 ] −4 and [AlO 4 ] −5 tetrahedron linked to each other by sharing oxygen atoms, forming a three-dimensional framework [ 20 ]. This structure confers essential properties, such as a large internal porosity that results in water retention, a uniform particle-size distribution that allows them to be easily incorporated and high cation-exchange capacity that retains nutrients [ 21 , 22 ]. Among the natural zeolites, clinoptilolite is the most abundant and commonly used in agricultural practices [ 18 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main applications in agriculture is their use as an additive to fertilizers, promoting the nutrient-retention capacity of the soils by improving the slower release of these elements for crop uptake [ 18 , 23 ]. Therefore, using zeolites and biochar as soil amendments and slow-release fertilizers is considered a sustainable approach that ameliorates soil physicochemical and biological properties, with a high potential to mitigate climate change [ 22 , 24 ]. However, as far as we know, the effect of biochar and zeolites, used as soil amendments, on olive yield, fruit and oil composition and quality has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective ways to maintain ensure adequate soil functionality and soil fertility, limiting the possibility of uptaken harmful compounds by plants is to provide enough soil organic matter, or soil organic carbon pools, in the soil [2]. It was also reported that the application of zeolite can be an effective soil amendment in the soil remediation process [3].…”
mentioning
confidence: 99%